Pengaruh Media Pembelajaran Gimkit Berbasis Game Edukasi Terhadap Hasil Belajar Siswa di MA Subulul Huda Darma - Damayanti, Alfina; Zakaria, Yoyo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study was to analyze the effect of using educational game-based learning media, namely Gimkit, at MA Subulul Huda Darma. The approach used in this study was a quasi-experimental design with a pretest-posttest design in the control group. The research sample consisted of two classes, namely an experimental class of 23 students who utilized Gimkit learning media, and a control class of 23 students who followed learning with conventional methods. To test the hypothesis, Paired Sample T-Test statistical test was used. The results of data analysis showed that the average value of the pretest in the experimental class was 58.91 with a posttest value of 81.09, while in the control class the pretest value was 51.74 and the posttest reached 75.22. This finding indicates that the use of Gimkit significantly improved student learning outcomes in the experimental class compared to the control class. Based on these results, it can be concluded that the application of Gimkit learning media has a positive influence on the achievement of student learning outcomes. In addition to improving academic achievement, Gimkit also increases student engagement, facilitates mastery of Indonesian History material in a more interesting and effective way, and develops higher order thinking skills, ranging from recall to analysis and evaluation, thus making Gimkit an effective innovative pedagogical strategy.